Domestication and Foreignization of Cultural Terms in Economics Textbook - Tarigan, Fatin Nadifa (Association of Language Teachers in Southeast Asia (ALTSA), 2018)
The research deals with domestication and foreignization strategies in translating culture specific items in economics bilingual textbook for junior high school students. The objectives of this study was to investigate the most frequent strategies used in translating culture specific items in economics bilingual textbook for junior high school. The research was conducted by using descriptive qualitative design. The data of this study were words, phrases, and clauses containing culture specific items. The data were collected through documentary technique. The technique of data analysis was interactive model. The finding of this study revealed that for domestication there were 25% cultural terms in the form of word and 46,4% in the form of phrase. While for foreignization, it was found only 21,5% in the form of word, and 7,1% in the form of phrase. It was not found the culture specific items in the form of clause both in domestication strategy and in foreignization strategy. The domestication was the dominant strategy used in translating cultural items in economics bilingual textbook. It indicates the translators tend to introduce Indonesian culture specific items into TL cultureKeywords: Domestication, foreignization, cultural terms, economics textbook